Evaluation of Dissolved Oxygen Concentration in Different Circulation Systems on Water Quality in Fish Pond - Yohana, Winda Y.; Nasution, Tulus I.; Wahyuningsih, Hesti; Matondang, Aprima A.; Margolang, Anggi R. (Journal of Applied Geospatial Information, 2024)
This study aims to evaluate the impact of different circulation systems on water quality parameters in tilapia rearing. Good water quality is very important in tilapia rearing so that tilapia can grow healthily and optimally. In this study, three different circulation systems were compared, namely a circulation system without a pump, a circulation system with one pump, and a circulation system with two pumps to increase the concentration of dissolved oxygen in the pond. The results of this study showed that CS III was able to maintain an efficient and stable DO concentration of around 7.5 to 8 ppm which also resulted in a stable pH value. Compared to CS I with a low DO concentration of about 3 ppm which impacted the pH value inefficiently. Also, CS II showed stable DO concentrations but decreased pH values. This shows that CS III can create more optimal environmental conditions for tilapia growth compared to other circulation systems. Furthermore, The consistent of DO concentration has an impact on other water quality parameters, namely pH, which is also consistent and stable, which is good for fish health.